2013
DOI: 10.1016/j.neuroimage.2013.07.040
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences in the development of brain mechanisms for processing biological motion

Abstract: Disorders related to social functioning including autism and schizophrenia differ drastically in incidence and severity between males and females. Little is known about the neural systems underlying these sex-linked differences in risk and resiliency. Using functional magnetic resonance imaging and a task involving the visual perception of point-light displays of coherent and scrambled biological motion, we discovered sex differences in the development of neural systems for basic social perception. In adults, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
66
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(70 citation statements)
references
References 77 publications
2
66
2
Order By: Relevance
“…Considering that autism and autistic traits occur at different rates across sexes (Baron-Cohen et al, 2001), and neural response to biological motion varies in a sex-dependent manner (Anderson et al, 2013), sex differences should specifically be targeted in future work.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering that autism and autistic traits occur at different rates across sexes (Baron-Cohen et al, 2001), and neural response to biological motion varies in a sex-dependent manner (Anderson et al, 2013), sex differences should specifically be targeted in future work.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Anderson et al (2013) found a negative association between a measure of social impairment associated with autism and activation to biological motion in frontal and partial regions in a non-clinical sample. However, these authors only considered traits in the social domain, and did not report descriptive statistics for this measure making it difficult to assess what range of the spectrum was captured in this study.…”
Section: Introductionmentioning
confidence: 99%
“…Another very important aspect to be considered in development is gender. Indeed, several studies have investigated the sex differences in the development of several neural functions during childhood (Koolschijn & Crone 2013;Anderson, Bolling, Schelinski, Coffman, Pelphrey et al, 2013), also during action observation (Shaw et al, 2011(Shaw et al, , 2012. In the present study we included a balance of male and female participants in both the children's and the adults' groups.…”
Section: Discussionmentioning
confidence: 99%
“…BMP with point-light displays can also convey a range of socially relevant information, including gender (Mather and Murdoch, 1994), affect (Pollick et al, 2001), personality traits such as trustworthiness (Heberlein et al, 2004), and identity (Troje et al, 2005; Jokisch et al, 2006). BMP has high inter-individual variability based on many different factors such as development conditions (Pavlova et al, 2001; Carter and Pelphrey, 2006), gender effect (Anderson et al, 2013; Pavlova et al, 2014), social cognition and motor imagery abilities (Miller and Saygin, 2013). In a recent study, Gilaie-Dotan et al (2013) found that the neuroanatomical structures of the posterior superior temporal sulcus and ventral medial prefrontal cortex were linked with biological motion detection performance.…”
Section: Introductionmentioning
confidence: 99%